Impact of Stray Voltage on Renewable Energy-based Farm in Pacific Island Country - F R Islam; Ravneel Prasad; Rezwanul Haque; Vishal Sharma (IAES Indonesian Section, 2020)
Recent advancements in solar technology offer an enormous opportunity for the people of Pacific Islands to use electricity from the off-grid solar system for both their energy needs and farming activities. However, a farm’s productivity and animal health might be seriously threatened if it experiences stray voltages caused by the improper grounding of its installed electrical systems. As a shift in the neutral point of an electrical system creates a current flow to the ground through conducting elements, the impacts of stray voltages need to be addressed from both technical and economic viewpoints. In this research, the effects of stray voltages passing through animals are explored using circuit designs for solar sources considering variable grounding resistances due to the different body resistances of various types of animals, and environmental and grounding design issues. A comparison of the stray voltages of two different sources (off-grid solar and traditional grid) with various configurations are conducted to determine their effects on a farm. Finally, their economic impacts together with possible techniques for mitigating them are explained.